Aplikasi Pupuk Organik Azolla dan Pupuk Hayati terhadap Kandungan N Tanaman, Serapan N Tanaman, dan Hasil Tanaman Padi Sawah Organik pada Inceptisols Jatinangor - Mieke Rochimi Setiawati; Diyan Herdiyantoro; Pujawati Suryatmana (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2023)
The need for adequate nutrition for organic rice cultivation is very important. It is necessary to look for various sources of nutrients apart from organic fertilizers from rice straw compost and manure. Azolla water ferns and solid or liquid biofertilizers shoud be used as an alternative in the way to increase plant nutrients in organic rice cultivation in paddy fields. This experiment aims to increase the yield of lowland rice plants which are cultivated organically for the first time through the application of organic fertilizer enriched with azolla and biofertilizers in the lowland rice fields of Inceptisols Jatinangor. The experiment was carried out at the Experimental Garden, Ciparanje, it’s belong to Faculty of Agriculture, Universitas Padjadjaran, Sumedang, West Java. The design used was a Randomized Block Design (RBD) with six treatments, namely organic fertilizer, organic fertilizer + Azolla, organic fertilizer + solid biofertilizer, organic fertilizer + Azolla + solid biofertilizer, organic fertilizer + liquid biofertilizer, organic fertilizer organic + Azolla + liquid biofertilizer. Each treatment repeated four times. The experimental results showed that the application of a combination of organic fertilizers and biofertilizers had an effect on lowland rice yields but had no significant effect on plant N content and N uptake of lowland rice plants in Inceptisols Jatinangor.